Progestin primed ovarian stimulation using corifollitropin alfa in PCOS women effectively prevents LH surge and reduces injection burden compared to GnRH antagonist protocol - Ting-Chi Huang; Mei-Zen Huang; Kok-Min Seow; Ih-Jane Yang; Song-Po Pan; Mei-Jou Chen; Jiann-Loung Hwang; Shee-Uan Chen (Scientific Reports, 2021)
Abstract Utilizing corifollitropin alfa in GnRH antagonist (GnRHant) protocol in conjunction with GnRH agonist trigger/freeze-all strategy (corifollitropin alfa/GnRHant protocol) was reported to have satisfactory outcomes in women with polycystic ovary syndrome (PCOS). Although lessening in gonadotropin injections, GnRHant were still needed. In addition to using corifollitropin alfa, GnRHant was replaced with an oral progestin as in progestin primed ovarian stimulation (PPOS) to further reduce the injection burden in this study. We try to investigate whether this regimen (corifollitropin alfa/PPOS protocol) could effectively reduce GnRHant injections and prevent premature LH surge in PCOS patients undergoing IVF/ICSI cycles. This is a retrospective cohort study recruiting 333 women with PCOS, with body weight between 50 and 70 kg, undergoing first IVF/ICSI cycle between August 2015 and July 2018. We used corifollitropin alfa/GnRHant protocol prior to Jan 2017 (n = 160), then changed to corifollitropin alfa/PPOS protocol (n = 173). All patients received corifollitropin alfa 100 μg on menstruation day 2/3 (S1). Additional rFSH was administered daily from S8. In corifollitropin alfa/GnRHant group, cetrorelix 0.25 mg/day was administered from S5 till the trigger day. In corifollitropin alfa/PPOS group, dydrogesterone 20 mg/day was given from S1 till the trigger day. GnRH agonist was used to trigger maturation of oocyte. All good quality day 5/6 embryos were frozen, and frozen-thawed embryo transfer (FET) was performed on subsequent cycle. A comparison of clinical outcomes was made between the two protocols. The primary endpoint was the incidence of premature LH surge and none of the patients occurred. Dydrogesterone successfully replace GnRHant to block LH surge while an average of 6.8 days of GnRHant injections were needed in the corifollitropin alfa/GnRHant group. No patients suffered from ovarian hyperstimulation syndrome (OHSS). The other clinical outcomes including additional duration/dose of daily gonadotropin administration, number of oocytes retrieved, and fertilization rate were similar between the two groups. The implantation rate, clinical pregnancy rate, and live birth rate in the first FET cycle were also similar between the two groups. In women with PCOS undergoing IVF/ICSI treatment, corifollitropin alfa/PPOS protocol could minimize the injections burden with comparable outcomes to corifollitropin alfa/GnRHant protocol.